Optimasi Multi Faktor pada Formula Karet Alam terhadap Gesekan Material Elastomer Karet Alam untuk Aplikasi Telapak Kaki Prostesis - Khafidh, Muhammad; Irfan, Afi Muhammad; Suryawan, Donny; Kistriyani, Lilis; Ismail, Rifky (TEKNIK, 2023)
Indonesia is the world's second-largest producer of natural rubber. Various products can be made of natural rubber. One of them is a foot prosthesis. An essential criterion for foot prosthesis is a significant value of friction force to prevent slip during usage. The present study optimizes natural rubber formulation to obtain the largest friction force value. A pin-on-disk tribometer is used to obtain friction force values. The optimization method used in the present study is Taguchi Method Orthogonal Array L9, while the contribution of each control factor to increase friction is carried out using ANOVA analysis. Four control factors are used in this study: the type of natural rubber, the percentage of silica powder, the percentage of sulfur, and the vulcanization temperature. Each control factor has three different levels. The test results showed that the optimum formulation to obtain the highest friction value is a mixture of concentrated natural rubber and instant natural rubber, 30 phr of silica powder, 5 phr of sulfur, and 150°C of vulcanization temperature. The friction force of the optimum formulation increases by 33% compared to the baseline formulation. ANOVA analysis shows that the vulcanization temperature is the most crucial factor in increasing the friction force, contributing 62.58%.